TAFSIR BI AL-RA’YI SEBAGAI SALAH SATU BENTUK PENAFSIRAN ALQURAN - Ba'asyien, Moh. Arsyad (State Institute of Islamic Studies (IAIN) Palu, 2005)
Tafsir bi al-Ra’yi is one of methods employed by ulama in interpreting the Holy Qur’an. The reason for interpreting the Holy Qur’an using reasoning is that there are many ayahs (verses of the Qur’an) encourage us to think . However, some of ulama prohibit the use of reason in interpreting the Qur’an because some of their interpretations are not compatible with the true massage of the Holy Qur’an. Consequently, their interpretation aims at supporting their own interest only.Key word: Tafsir bi al-Ra’yi, bentuk penafsiran, Alquran